2012
DOI: 10.1186/1471-2458-12-917
|View full text |Cite
|
Sign up to set email alerts
|

ORCHIDS: an Observational Randomized Controlled Trial on Childhood Differential Susceptibility

Abstract: BackgroundA central tenet in developmental psychopathology is that childhood rearing experiences have a major impact on children’s development. Recently, candidate genes have been identified that may cause children to be differentially susceptible to these experiences (i.e., susceptibility genes). However, our understanding of the differential impact of parenting is limited at best. Specifically, more experimental research is needed. The ORCHIDS study will investigate gene-(gene-)environment interactions to ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 51 publications
(53 reference statements)
2
28
0
4
Order By: Relevance
“…Data were collected in two cohorts from November 2012–2013 through November 2013–2014. Detailed information about the sample and sampling appears elsewhere (Chhangur, Weeland, Overbeek, Matthys, & Orobio de Castro, ; Weeland, Chhangur et al., in press). Using a randomized control design, the ORCHIDS study addresses the differential effectiveness—across children with varying temperamental and genetic characteristics—of the IY program in reducing externalizing behavior in 4‐ to 8‐year‐old children showing moderate to high levels of such problems by enhancing a warm parent–child relationship through child‐directed play; coaching of social, emotional, and academic skills; praise and rewards; effective limit setting; and handling (e.g., ignore and time‐out techniques).…”
Section: Methodsmentioning
confidence: 99%
“…Data were collected in two cohorts from November 2012–2013 through November 2013–2014. Detailed information about the sample and sampling appears elsewhere (Chhangur, Weeland, Overbeek, Matthys, & Orobio de Castro, ; Weeland, Chhangur et al., in press). Using a randomized control design, the ORCHIDS study addresses the differential effectiveness—across children with varying temperamental and genetic characteristics—of the IY program in reducing externalizing behavior in 4‐ to 8‐year‐old children showing moderate to high levels of such problems by enhancing a warm parent–child relationship through child‐directed play; coaching of social, emotional, and academic skills; praise and rewards; effective limit setting; and handling (e.g., ignore and time‐out techniques).…”
Section: Methodsmentioning
confidence: 99%
“…We used data from the Observational Randomized Trial on Childhood Differential Susceptibility (ie, The ORCHIDS study). 20 This is a preregistered randomized controlled trial of the Incredible Years Parenting Program in an indicated prevention setting (ie, children were screened for disruptive behavior; Trial 3594, ORCHIDS, https://www.trialregister. nl).…”
Section: Methodsmentioning
confidence: 99%
“…The protocol and full study details are reported elsewhere. 20,21 Participants For this study, families with children aged 4 to 8 years were recruited through community records and screened on elevated levels of disruptive child behavior (ie, >75 th percentile on the Eyberg Child Behavior Inventory 21 ). In total, 387 parentÀchild dyads participated (197 intervention and 190 control).…”
Section: Methodsmentioning
confidence: 99%
“…In de tweede fase werden alle gezinnen die in aanmerking kwamen voor het onderzoek uitgenodigd voor deelname aan de RCT: Observational Randomized Trial on Childhood Differential Susceptibility (ORCHIDS-studie) (Chhangur et al 2012). Van de gezinnen die in aanmerking kwamen, werd ongeveer 60 % telefonisch bereikt (n = 850), en 46 % van de bereikte gezinnen deed uiteindelijk mee met het onderzoek (zie fig.…”
Section: Methode Designunclassified